Analysis of Field Work Practice Issues in the Automotive Light Vehicle Engineering Expertise Concentration at SMK Negeri 4 Serang City - Iqrom, Muhamad Nur; Iman, Atep; Ramdani, Sulaeman Deni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to identify the challenges faced by students during the Field Work Practice (PKL) in the Automotive Light Vehicle Engineering (TKRO) program at SMK Negeri 4 Serang City. The focus of the study includes aspects of planning, implementation, assessment, as well as monitoring and evaluation of the PKL. The method used is descriptive quantitative, with data collection through questionnaires given to 63 students of class XII TKRO and interviews with supervising teachers. The results of the study show that students face various challenges, such as the mismatch between the PKL location and their field of expertise, insufficient preparation before the PKL, and the discrepancy between school material and industry practices. However, the planning, implementation, and evaluation of the PKL were rated as good to excellent. The industry's assessment of the students was also positive, but monitoring activities by the school are still limited due to resource constraints. This study recommends strengthening school-industry cooperation, improving preparation and monitoring systems, and placing students in PKL locations that align with their competencies. These findings are expected to serve as a reference in efforts to improve the quality of PKL implementation and the job readiness of vocational school graduates.